Epidemiological aspects of cutaneous leishmaniasis in the Iguazú falls area of Argentina - Salomón, Oscar Daniel (2009)
Over the last three decades the incidence of American cutaneous leishmaniasis (ACL) has increased sharply in Argentina and throughout the world. In the Iguazú Falls area, on the border between Brazil and Paraguay, the incidence of human ACL has risen since 2004. Most of the 36 cases of human ACL reported until 2005 have involved males over 15 years old (75%) infected during deforestation to establish individual farms. Captures carried out in primary forest, periurban areas, and deforested land sites yielded 18,438 sand flies belonging to 13 species; the most prevalent species were Lutzomyia (Nyssomyia) whitmani (87.4%) and Lutzomyia (Mygonemyia.) migonei (7.6%). Cluster analysis was used to group traps according to species and abundance of sand flies. The group of traps located in recently deforested places, in pig and chicken dwellings of houses where ACL cases had been reported in the past, and at one house with an active ACL case, had the highest abundance of Lu. whitmani and Lu. whitmani + Lu. migonei as well as the highest ratio of Lu. whitmani/Lu. migonei. Leishmania sp. infections, both in Lu. whitmani, in Lu. quinquefer, and in smears from human cases were detected by DNA kinetoplast amplification using a generic PCR protocol. The risk of ACL outbreak in the Iguazú Falls area is still associated with economic and leisure activities in primary-secondary forest, including deforestation, rural settlements, fishing, hunting, and ecotourism. In addition, the risk of periurban transmission seems likely, and this is discussed within the framework of surveillance and prevention strategies. © 2008 Elsevier B.V. All rights reserved.